ナンキョク タイリュウケン チュウ ノ チョウビショウ リュウシ ノ キハツトクセイ ト ソノ キセツ ヘンカ - 原, 圭一郎; ハラ, ケイイチロウ; 長田, 和雄; オサダ, カズオ; 西田, 千春; ニシダ, チハル; 矢吹, 正教; ヤブキ, マサノリ; 林, 政彦; ハヤシ, マサヒコ; 山内, 恭; ヤマノウチ, タカシ; et al. (2010)
P(論文) 第46-47次日本南極地域観測隊で,超微小粒子の粒径分布とその揮発特性の連続観測を実施した.夏季には超微小粒子のほとんどは揮発性粒子で,硫酸,メタンスルホン酸,硫酸塩で構成されていた.夏には超微小粒子域の非揮発性粒子の割合は20% だったが,冬季には90% を超すこともあった.冬季の超微小粒子のほとんどは海塩粒子であり,海氷上で組成分別をした海塩粒子も含まれていた.南極大陸内陸部上空から昭和基地(沿岸部)に空気塊が輸送される時には,冬季にも揮発性粒子の割合が減少していた. The Size distribution and volatility of ultrafine aerosol particles were measured at Syowa Station during the 46-47 Japanese Antarctic Research Expeditions. During the summer, most of the ultrafine particles were volatile particles, which were composed of H_2SO_4, CH_3SO_3H and sulfates bi-sulfates. The abundance of non-volatile particles was ～ 20% during the summer, increasing to>90% in winter-spring. Non-volatile particles in winter were dominantly sea-salt particles. Some ultrafine sea-salt particles might be released from sea-ice. When air mass was transported from the free troposphere over the Antarctic continent, the abundance of non-volatile particles dropped to<30% even in winter. departmental bulletin paper